Response of tertiary addictions services to opioid dependence during the COVID-19 pandemic. (4th December 2021) - Hennigan, K.; Corrigan, N.; Killeen, N.; Scully, M.; Keenan, E.
Abstract : The emergence of the COVID-19 pandemic has presented the addiction services with an unprecedented set of challenges. Opioid users are particularly vulnerable because of their high level of pre-existing health problems and lifestyle factors. In order to minimise their risks to self and to others in the current Covid-19 crisis, addiction services sought to urgently identify vulnerable individuals, and induct them into opioid substitution treatment (OST) promptly. Additionally, several guidelines were created and regularly updated by the health and safety executive (HSE) for any healthcare staff working with opioid users. These include guidance documents, to facilitate prompt induction of patients onto the OST programme, the prescribing of naloxone to all patients at risk of overdose, eConsultation, medication management for those in self-isolation, and the delivery of injecting equipment. The guidance documents and resources will provide a template for a new way of working for the sector during these challenging times and into the future.